2000
DOI: 10.1002/(sici)1099-1700(200004)16:3<161::aid-smi847>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Stress management by psychosomatic training: effects ofChunDoSunBup Qi-training on symptoms of stress: a cross-sectional study

Abstract: We examined the effects of ChunDoSunBup (CDSB) Qi‐training, one of Korea's traditional forms of psychosomatic training, on stress coping ability by cross‐sectional investigation using the Symptoms of Stress (SOS) inventory. Four types of groups—normal health (n=74) and three groups of Qi‐trainees (group Q1: subjects with CDSB Qi‐training for 1–4 months, n=64; Q2: 5–12 months, n=50; Q3: more than 13 months, n=66)—participated in this study. Qi‐trainees with over 13 months training had significantly lower scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Positive selfsuggestions probably give support and speed up the healing process. Studies have also shown that practicing qigong regularly brings improvement in psychological well-being, relaxation, physical ability, as well as relieving psychosomatic and stress-related disorders (Hui et al 2006;Lee et al 2000;Yong and Lee 2005). Our findings from the interviews indicated that improvements in qi xi (energy and vitality), moods, flexibility of muscles and joints were commonly reported by the qigong subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive selfsuggestions probably give support and speed up the healing process. Studies have also shown that practicing qigong regularly brings improvement in psychological well-being, relaxation, physical ability, as well as relieving psychosomatic and stress-related disorders (Hui et al 2006;Lee et al 2000;Yong and Lee 2005). Our findings from the interviews indicated that improvements in qi xi (energy and vitality), moods, flexibility of muscles and joints were commonly reported by the qigong subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of chan mi gong on the regulation of mood, in particular stress, anxiety, and quality of life, to the best of our knowledge, have never been investigated before. Previous qigong studies have documented that qigong is effective in reducing stress (He et al 1999;Lee et al 2003b;Lee et al 2000), treating anxiety and depression (Pavek 1988;Shan et al 1989), reducing adrenocorticotropic hormone, cortisol, and aldosterone levels (Lee et al 2004a), reducing norepinephrine and epinephrine (Lee et al 2003b); improving mood (Lee et al 2001), and enhancing the immune system (Lee et al 2003a). Qigong distinguishes itself from other therapies in terms of its roots in TCM concepts and its emphasis on qi (vital energy) and yi (intention power), which are regarded as an effective intervention to manage mood states and enhance body-mind well-being (Lehrer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…20 Concentration meditation, a component of qigong practice, also decreases stress. 21,22 The practice of slow, deep breathing patterns similar to those employed in this qigong set have been demonstrated effective in reducing blood pressure in both mild hypertensive and normotensive subjects, through a mechanism thought to be related to decreased sympathetic activity. 23 Finally, stress-related endogenous chemicals, including norepinephrine 11 and cortisol, 24 were reported to be reduced by qigong.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, Qigong has been found to reduce stress [24,25], anxiety [26], and depression [27] as well as to improve physical activity and balance [28]. Since patients with burnout often report exhaustion and low energy levels, Qigong would be a favorable method in their rehabilitation.…”
Section: Introductionmentioning
confidence: 99%